Artistic loops in environment memory - Alonso Atienza, Loreto (Re-visiones, 2024)
At a time when much of our life depends on the satisfactory exchange of networked digital data, socially shared memory could be interpreted as a floating environment of data and procedures to which we only have limited access. Cultural practices and artistic projects operating in this environment, proposing aesthetic positions and activating critical issues. This article shows the concept of environment memory, associated with technological innovations, in the omnipresence of the collective dream that Benjamin links with modernity and cinema. We will address this potential evolution of what we deem to be environmental memory through three fictional narratives, Nineteen Eighty Four, Big Brother and The Congress. In the second part of the paper we elaborate on some dimensions of this environment memory, considering the current folksonomic condition and data circulation on the Internet. And we will focus on some relevant strategies and artistic trends, starting from what we define as loops in the transmission channels and the consumption of resources (Parasite Loop, Interactive estrangement Loop, Infinite reproduction Loop, Prosurfer Loop and Popinternet Loop), which, among other things, seem to question what is proper and improper in what we interpret as environment memory.